The role of the reports of the Federal Financial Supervision Bureau in addressing tax evasion in mixed companies: applied research in the General Tax Author it (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to highlight the role of the National Audit Office in detecting cases of tax evasion for a sample of mixed sector companies and the extent of the contribution of the National Audit Office in finding remedies for cases of tax evasion, where the reports issued to the NAO for five mixed joint stock companies represented by (Al-Kindi Company for the production of vaccines and veterinary medicines, the National Company for Chemical Industries, Al-Mansour Hotel Company, Babylon Hotel Company and Ishtar Hotel Company)were analyzed for the observations proven in the reports of the Bureau issued by the Bureau for those companies,  Accordingly, several conclusions were reached, the most important of which wereMost of the companies in the research sample did not deduct income tax from their employees for several years, or they did not deduct it and did not hand it over to the General Tax Authority. Therefore, it is necessary to tighten the procedures on violators so as not to repeat the situation.  Also, some companies did not pay profit taxes and withheld the amounts in the calculation of tax allocations, which caused the delay in tax deductions, which is a violation of Article (14) of the Income Tax Law No. (113) of 1982, as amended.